Hit hard and early: Can the march of psoriasis be halted? - Sridhar Jandhyala (Wolters Kluwer Medknow Publications, 2013)
Psoriasis is increasingly considered a systemic disease with comorbidities. There is sufficient evidence that systemic inflammation lies at the heart of these developments. Considering the chronic nature of psoriasis and its comorbidities, timely manipulation of systemic inflammation could avert both mortality and morbidity. Data from retrospective studies suggest that aggressive treatment of psoriasis with traditional systemic agents and/or biologic drugs improves health outcomes. To maximize treatment outcomes, severe psoriasis needs to be managed as a systemic disease with likely comorbidities.